Rescue Stenting for Failed Mechanical Thrombectomy in Acute Ischemic Stroke: A Multicenter Experience. Issue 4 (April 2018) - Chang, Yoonkyung; Kim, Byung Moon; Bang, Oh Young; Baek, Jang-Hyun; Heo, Ji Hoe; Nam, Hyo Suk; Kim, Young Dae; Yoo, Joonsang; Kim, Dong Joon; Jeon, Pyoung; Baik, Seung Kug; Suh, Sang Hyun; et al.
Abstract : Background and Purpose—: Effective rescue treatment has not yet been suggested in patients with mechanical thrombectomy (MT) failure. This study aimed to test whether rescue stenting (RS) improved clinical outcomes in MT-failed patients. Methods—: This is a retrospective analysis of the cohorts of the 16 comprehensive stroke centers between September 2010 and December 2015. We identified the patients who underwent MT but failed to recanalize intracranial internal carotid artery or middle cerebral artery M1 occlusion. Patients were dichotomized into 2 groups: patients with RS and without RS after MT failure. Clinical and laboratory findings and outcomes were compared between the 2 groups. It was tested whether RS is associated with functional outcome. Results—: MT failed in 148 (25.0%) of the 591 patients with internal carotid artery or middle cerebral artery M1 occlusion. Of these 148 patients, 48 received RS (RS group) and 100 were left without further treatment (no stenting group). Recanalization was successful in 64.6% (31 of 48 patients) of RS group. Compared with no stenting group, RS group showed a significantly higher rate of good outcome (modified Rankin Scale score, 0–2; 39.6% versus 22.0%; P =0.031) without increasing symptomatic intracranial hemorrhage (16.7% versus 20.0%; P =0.823) or mortality (12.5% versus 19.0%; P =0.360). Of the RS group, patients who had recanalization success had 54.8% of good outcome, which is comparable to that (55.4%) of recanalization success group with MT. RS remained independently associated with good outcome after adjustment of other factors (odds ratio, 3.393; 95% confidence interval, 1.192–9.655; P =0.022). Follow-up vascular imaging was available in the 23 (74.2%) of 31 patients with recanalization success with RS. The stent was patent in 20 (87.0%) of the 23 patients. Glycoprotein IIb/IIIa inhibitor was significantly associated with stent patency but not with symptomatic intracranial hemorrhage. Conclusions—: RS was independently associated with good outcomes without increasing symptomatic intracranial hemorrhage or mortality. RS seemed considered in MT-failed internal carotid artery or middle cerebral artery M1 occlusion.